Why G20 India could be a game-changer for midwives and nurse's leadership in global health - Kaveri Mayra; Deepika Saluja; Shubha Nagesh (The Lancet Regional Health - Southeast Asia, 2024)
The upcoming G20 meeting in India presents a unique opportunity for the country to further cement its global health leadership record and pave the way internationally to advance the gender equality agenda.
Keywords: Primary health care; Wealth & wellness centre; Public health; Community